2016
DOI: 10.3389/fmicb.2016.01868
|View full text |Cite
|
Sign up to set email alerts
|

A DegU-P and DegQ-Dependent Regulatory Pathway for the K-state in Bacillus subtilis

Abstract: The K-state in the model bacterium Bacillus subtilis is associated with transformability (competence) as well as with growth arrest and tolerance for antibiotics. Entry into the K-state is determined by the stochastic activation of the transcription factor ComK and occurs in about ∼15% of the population in domesticated strains. Although the upstream mechanisms that regulate the K-state have been intensively studied and are well understood, it has remained unexplained why undomesticated isolates of B. subtilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 65 publications
4
36
0
Order By: Relevance
“…The comQ :: kan mutant (BM1400) was constructed by transforming the B. subtilis PS-216 with the DNA isolated from the strain BD2876 ( Tortosa et al, 2001 ). The degQ :: tet mutant was constructed by transforming the genomic DNA from the strain BD7123 ( Miras and Dubnau, 2016 ) to appropriate PS-216 strains. Mutants with P aprE-gfp were constructed by transforming O8G57 genomic DNA ( Veening et al, 2008 ) into appropriate PS-216 strains.…”
Section: Methodsmentioning
confidence: 99%
“…The comQ :: kan mutant (BM1400) was constructed by transforming the B. subtilis PS-216 with the DNA isolated from the strain BD2876 ( Tortosa et al, 2001 ). The degQ :: tet mutant was constructed by transforming the genomic DNA from the strain BD7123 ( Miras and Dubnau, 2016 ) to appropriate PS-216 strains. Mutants with P aprE-gfp were constructed by transforming O8G57 genomic DNA ( Veening et al, 2008 ) into appropriate PS-216 strains.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it was shown that DegQ positively regulates fengycin production [28]. In fact, DegQ stimulates the phospho-transfer within two component system DegS-U [27,34]. As a result, the phosphorylated DegU-P version causes higher expression of ppsABCDE operon [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that DegQ positively regulates plipastatin production [30]. In fact, DegQ stimulates autophosphorylation of DegS sensor kinase resulting in enhanced phospho-transfer to DegU response regulator [29,35]. As a result, the phosphorylated and activated DegU-P version causes higher expression of ppsABCDE operon and increases the plipastatin production [36].…”
Section: Discussionmentioning
confidence: 99%